The Determinants of Financial Performance in Life Insurance Sector in India - Mulchandani, Kalyani; Sitlani, CS Manish; Mulchandani, Ketan (Asian Journal of Empirical Research, 2017)
This paper attempts to examine the relationship between financial performance and their determinants in the case of Indian life insurance sector. This study is carried out using Correlation and Multiple Regression Analysis for 23 out of 24 companies for 10 years from 2009-10 to 2014-15. The financial performance is indicated by Return on Assets (ROA) and the independent variables chosen are commission, expenses, liquidity, size, solvency ratio, surplus (deficit)/policy holder’s liability, tangibility and underwriting risk. The quality of data was assessed using Autocorrelation, Heteroskedasticity, Multicollinearity. The results of the model indicated that commission, size and surplus (deficit)/policy holder' are significantly related to financial performance, commission is negatively related and size and surplus(deficit)/policy holder’s liability are positively related to financial performance whereas other factors expenses, liquidity, solvency ratio, tangibility and underwriting risk are not significant related to financial performance.